Helminths of the teiid lizard Kentropyx calcarata (Squamata) from an Amazonian site in western Brazil - Avila, R. W. [UNESP]; da Silva, R. J. [UNESP] (Cambridge University Press, 2009)
Despite being conspicuous members of neotropical lizard communities, aspects of the life history of many teiid lizard species are poorly known, especially endoparasites infecting the genus Kentropyx. We studied seven specimens of K. calcarata collected at an Amazonian site in Mato Grosso state, Central Brazil in 2007. Four species of helminth were recovered: Oswaldocurzia sp., Piratuba digiticauda, Physaloptera retusa and Physalopteroides venancioi. Piratuba digiticauda, a body-cavity, parasite had the highest prevalence (42.9%), whereas the stomach parasites P. Uenancioi and P. retusa presented the highest intensity of infection and abundance, respectively. Moreover, this is the first report of Oswaldocruzia sp., P. digiticauda and P. venancioi in K. calcarata and new locality records for all nematodes were assigned.